ASSCOCIATION BETWEEN HEMISPHERE LESIONLOCATION AND LEVEL OF DEPRESSION IN ISCHEMIC STROKE PATIENTS - Beatrice Angela Buulolo*, Habibah Hanum Nasution, Wika Hanida Lubis & Iskandar Nasution (International Journal of Research Science and Management, 2019)
Introduction: Depression is a common post-stroke complication. Nearly 30% of post-stroke patients can develop depression, either in the early or late stages. Specific locations of lesions in the brain, including hemispheric lesions is said to have a close relationship with the occurrence of post-stroke depression. Aim: To determine the relationship between the location of hemispheric lesions in ischemic stroke patients and level of post-stroke depression. Methods: This cross-sectional study was conducted at Adam Malik and USU Hospital in November 2018 to January 2019 consecutively for 40 ischemic stroke patients who met inclusion criteria. Patients were subjected to history and assessment of depression levels based on DSM -V and BDI-II questionnaire. Data was analyzed using Chi-square and Annova tests. Results: Of 20 right hemisphere lesions patients, 9(45%) had mild, 7(35%) moderate, and 4(20%) severe depression. While 20 left hemisphere lesions patients, 3(15%) had mild, 5(25%) moderate, and 12(60%) severe depression. There was a significant relationship between location of hemispheric lesions and level of depression in ischemic stroke patients where left hemisphere lesions were at higher risk for more severe depression (p=0.026). Conclusion: Left hemisphere lesions can be a predictive factor in the occurrence of severe post-stroke depression in ischemic stroke patients